Benzoate Anion‐Intercalated Layered Cobalt Hydroxide Nanoarray: An Efficient Electrocatalyst for the Oxygen Evolution Reaction. Issue 20 (13th September 2017) - Ge, Ruixiang; Ren, Xiang; Ji, Xuqiang; Liu, Zhiang; Du, Gu; Asiri, Abdullah M.; Sun, Xuping; Chen, Liang
Abstract: Efficient oxygen evolution reaction (OER) catalysts are highly desired to improve the overall efficiency of electrochemical water splitting. We develop a benzoate anion‐intercalated layered cobalt hydroxide nanobelt array on nickel foam (benzoate‐Co(OH)2 /NF) through a one‐pot hydrothermal process. As a 3 D electrode, benzoate‐Co(OH)2 /NF with an expanded interlayer spacing (14.72 Å) drives a high OER catalytic current density of 50 mA cm −2 at an overpotential of 291 mV, outperforming its carbonate anion‐intercalated counterpart with a lower interlayer spacing of 8.81 Å (337 mV overpotential at 50 mA cm −2 ). Moreover, this benzoate‐Co(OH)2 /NF can maintain its catalytic activity for 21 h. Abstract : Layer it up ! Benefiting from expanded interlayer spacing and nanoarray structure, benzoate anion‐intercalated layered cobalt hydroxide nanobelt array behaves as a highly efficient catalyst for the oxygen evolution reaction, driving a large current density a low overpotential in alkaline media.